2017
DOI: 10.1007/s11547-017-0736-8
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the appropriate side for subcutaneous port catheter placement in patients with mastectomy: ipsilateral or contralateral?

Abstract: SPC related complications do not differ in regard to ipsilateral or contralateral side selection on mastectomized patients with breast cancer and lymph node dissection. SPCs can be implanted on ipsilateral or contralateral sides of the operation in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, in recent years, more and more studies demonstrated that there was no difference in port complications or lymphedema rates between patients who had ports placed on the ipsilateral side compared with the contralateral side for breast cancer treatment. 22,27 There are still some problems to be addressed further. First, in our study, there are about half of the patients with ipsilateral subclavian PC received radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in recent years, more and more studies demonstrated that there was no difference in port complications or lymphedema rates between patients who had ports placed on the ipsilateral side compared with the contralateral side for breast cancer treatment. 22,27 There are still some problems to be addressed further. First, in our study, there are about half of the patients with ipsilateral subclavian PC received radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some traditional surgeons take the opinion that the veins of ipsilateral sick side should avoid blood drainage and central venous catheter insertion to aggravate lymphedema. However, in recent years, more and more studies demonstrated that there was no difference in port complications or lymphedema rates between patients who had ports placed on the ipsilateral side compared with the contralateral side for breast cancer treatment 22,27 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations